Microphysical properties and thermodynamic phase of Arctic low-level clouds from in-situ aircraft measurements - Moser, Manuel (2024)
The Arctic region is experiencing the most pronounced mean temperature rise of any region on Earth, causing drastic changes in the regional and global climate. Current investigations seek to elucidate the processes responsible for the intensified anthropogenic temperature change. Clouds in particular are suspected to play a crucial role in the Arctic climate feedback mechanisms. Clouds cool or warm the surface, depending on their ambient condition, microphysical properties, and thermodynamic phase. The gap in knowledge of microphysical cloud processes is particularly pronounced for mixed-phase clouds, which contain supercooled droplets with coexisting ice crystals and are frequently encountered in the lower part of the atmosphere at high latitudes. To better assess the role of clouds in the Arctic climate system, a comprehensive in-situ cloud data set of low-level Arctic clouds was measured within the scope of this thesis, using an advanced setup of airborne in-situ cloud probes. The airborne in-situ cloud measurements were carried out over the northern Fram Strait between Greenland and Svalbard in spring 2019, summer 2020, and spring 2022. In total, 2676 min of low-level in-situ cloud observations were performed during 33 research flights above the sea ice and the open Arctic ocean with the research aircraft Polar 5 and Polar 6 of the Alfred Wegener Institute. At first, the in-situ cloud data from spring 2019 and summer 2020 are combined to investigate the distribution of particle number concentration N, effective diameter Deff, and cloud water content CWC (liquid and ice) of Arctic low-level clouds, measured at latitudes between 76 °N and 83 °N. A method is developed to quantitatively derive the occurrence probability of their thermodynamic phase from the combination of microphysical cloud probe and Polar Nephelometer data. The changes in cloud microphysics and cloud thermodynamic phase are investigated related to the ambient meteorological situation in spring and summer, and the effects of surface conditions, ...